Common and rare CARD14 gene variants affect the antitumour necrosis factor response among patients with psoriasis. (1st July 2016) - Coto‐Segura, P.; González‐Fernández, D.; Batalla, A.; Gómez, J.; González‐Lara, L.; Queiro, R.; Alonso, B.; Iglesias, S.; Coto, E.
Summary: Background: The CARD14 gene encodes a protein that enhances nuclear factor (NF)‐κB activation and the upregulation of proinflammatory pathway genes. CARD14 is upregulated in psoriatic vs. normal skin, and rare and common CARD14 variants have been associated with the risk of developing psoriasis. Our hypothesis was that CARD14 variants could also influence the response to antitumour necrosis factor (anti‐TNF) therapies among patients with psoriasis. Objectives: To determine whether CARD14 gene variants were linked to a significant positive anti‐TNF response in patients with psoriasis. Methods: DNA from 116 patients with psoriasis was subjected to next‐generation sequencing of the CARD14 gene. All of the patients were nonresponders or had contraindications to conventional systemic treatments. Results: A reduction of at least 75% in Psoriasis Area and Severity Index (PASI 75) at week 24 was considered a positive response to treatment. In total 116 patients (79 responders and 37 nonresponders) were next‐generation sequenced, and we identified five nucleotide variants that would result in missense amino acid changes. These variants were determined in all of the patients, and allele and genotype frequencies were compared between the two groups. We found a significantly higher frequency of rs11652075 CC (p.Arg820Trp) among the group with a positive response ( P = 0.01, odds ratio 3.71, 95% confidence interval 1.30–10.51). Furthermore, among responders, six patients were heterozygous carriers of the rare p.Glu422Lys variant, and two patients were heterozygous for p.Arg682Trp ( P = 0.04). Conclusions: The common CARD14 p.Arg820Trp variant might have a significant effect on the response to anti‐TNF therapies among patients with psoriasis. In addition, rare CARD14 missense variants could also predispose to a better response.